A 'Suitable Person': an 'insider' perspective. (June 2015) - Coles, Barbara; Williams, Val; Tarleton, Beth
<x xml:space="preserve">Abstract</x> Accessible Summary The purpose of this article is to demonstrate how 'insider' research can make an effective contribution to policy debates. It draws on a study which looked at the experiences of twelve parents in England who manage a Direct Payment for an adult child who has a learning disability and complex support needs. This article matters to people with learning disabilities because it reveals some of the challenges faced by some parents who are managing Direct Payments on their behalf. Summary This article draws on a doctoral study carried out across seven counties in England which focused on twelve parents' experiences of carrying out the role of a 'suitable person' ('SP') by managing a direct payment for an adult child (living in her/his own home) who has severe learning disabilities, autism and very complex support needs. Evidence came from naturally occurring qualitative data using (auto) ethnography. The research exposed how vital these parents' expertise and skills are to their adult children, but also how they themselves are being used within the care system. This article considers whether research has greater impact if a researcher who has direct experience of the research problem has conducted it. It argues that 'insider' research can uncover a unique perspective of some of the issues that directly affect the lives of 'SP'. In terms of 'impact', how seriously such research is taken, especially if the findings run counter to much of the existing literature, as it did in this study, remains to be seen.